The influence of work discipline, work environment and motivation on the performance of employees of the Kerinci District Education Office - Wazirman Wazirman; Ikhwan Ikhwan; Heraldo Sondakh; Meri Siswita (Jurnal Mantik, 2023)
This study aims to determine the effect of work discipline, work environment and motivation on the performance of employees of the Kerinci Regency Education Office. This study uses a quantitative research type method, where the sampling technique uses total sampling technique, with a sample size of 40 employees of the Kerinci Regency Education Office. The analysis technique is multiple regression analysis. The results of this study are both partially and simultaneously, work discipline, work environment and motivation to the performance of employees of the Kerinci Regency Education Office.